رفع ضوضاء صورة متكيف باالعتماد على مرشحات MACWM و NLEM - كاظم حمود Haider; عبداللطيف عبدالجبار Huda; عبدعلي عبد الكاظم Ahmed; حسن هاشم Sahar (مجلة كلية التربية, 2020)
High range types of noise can infect and corrupt digital images. Of these Noise types is the resulted from errors in the image acquisition process. This error change pixel values that not reflect the true intensities and image details vision. Several ways that noise can be introduced into an image, most of them depending on how the image is created or transmit through the network. In this paper, new proposed modifications added to Modified Adaptive Center Weighted Median filter MACWM to achieve the high accuracy in noise detection and removing especially when image corrupted by multi noise types. None Local Euclidean Median (NLEM) and Mean filters were added in these proposed modifications improved the noise wide spectrum detection. Good vision results produce from experiment the proposed system with less blur.